P184 3D endoanal ultrasound: diagnosis and follow-up of anal fistulas in Crohn's disease. (16th January 2018) - Orlandi, S; Massella, A; Variola, A; Fortuna, M; Geccherle, A
Abstract: Background: Perianal Crohn's disease (PCD) requires a multidisciplinary approach. As an optimal management of the disease, it is critical to have a complete study of fistula, including clinical assessment of external opening and digital rectal exploration (DRE), endoscopic evaluation and Magnetic Resonance Imaging (MRI) measurements to define fistula's anatomy and The presence of abscesses. Methods: 3D-Endoanal Ultrasound (3D-EAUS) shows a good concordance with surgery in detection of primary and secondary fistulas and has a high sensitivity and specificity for the internal opening diagnosis. In our study we aimed to test the role of 3D-EAUS in the management of Crohn's disease perianal fistulas. Results: 47 patients (patients) with complex PCD underwent surgery: 8 patients were treated using video-assisted anal fistula treatment (VAAFT) technique combined with advanced flap repair and closure of internal opening, 13 patients were treated with lay open surgery and 26 patients underwent fistulectomy and seton placement. One month after surgery all the patients received Infliximab (IFX) therapy. During the induction period patients underwent proctological visit and 3D-EAUS. On maintenance IFX therapy we performed only a DRE and anoscopy. Due to detection of abscess, an absolute contraindication to IFX, ultrasound examination has been crucial in stopping the biologic therapy in 3% of patients. Conclusions: 3D-EAUS is a cost-effective, useful and simple technique for the monitoring of PCD patients undergoing surgery and successively treated with IFX.